A computerized method for generating Islamic star patterns. (April 2018) - Khamjane, Aziz; Benslimane, Rachid
Abstract: In this paper, we will present a method based on the symmetry group theory to construct Islamic star patterns. The method builds star patterns using one or multiple kinds of stars/rosettes from a fundamental region of a given symmetry group and a few intuitive parameters. This paper explains the procedure used in the arrangement and construction of the stars/rosettes within the fundamental region. Given a symmetry group, the method begins by constructing, within the fundamental region, the minimal essential information (template motif) needed to generate a particular symmetry type. The constructed template motif, on which we operate a set of transformations that depend on the symmetry group, results in the unit motif (content of the unit cell). Finally, the entire pattern is obtained by replicating the unit motif in a suitable net. The paper gives a set of generated patterns for the most encountered symmetry groups in Islamic geometric art. Graphical abstract: Highlights: A generation method of Islamic star patterns is proposed. The steps to construct the template motif within the fundamental region are detailed. Patterns with overlapped rosettes are treated. A wide variety of patterns is obtained by changing the motif parameters. A comparative study is done to determine the appropriate parameters to obtain historical patterns.